Injury prevention through balance and coordination analysis in elite basketball players - de Campos Gutierrez de Calderon, A.; Lopez Roman, A.; Dominguez Munoz, C.; Lopez-Illescas Ruiz, A. (Archivos de medicina del deporte, 2008)
Within basketball, injuries most commonly appear in lower limbs. In the Spanish National League, these are up to 46,13% of the whole; within the NBA, there ratio is higher, even 57,3% (Moraes Menezes, 2003). Muscular instability in lower limbs, and coordination and balance impairments are injury risk factors. Using devices which can show such problems in these motor skills is essential in the medical evaluation of these sportsmen, in order to prevent such injuries. Objectives: 1. Find out whether Neurocom Balance Master is a suitable device to assess and discriminate balance, coordination and postural skills in elite basketball players. 2. Find out which tests and parameters are better to assess impairments regarding balance and coordination. 3. Assess balance on stable and unstable surfaces, analysing re-balance ability and skills. Materials and methods: Neurocom Balance Master System Posturographer. Subjects: 30 healthy elite basketball players (age range 19 - 25 years) Method: 1st : General and specific warm up. 2nd : Protocol. (Use of statistics pack SPSS. 15.00). Results: 1. In the LOS test, the Movement Velocity was higher in basketball players than in the control group. ' 2. In the CTSIB test (over foam with closed eyes), the COG Sway Velocity of basketball players is lower than in the control group. Data and results will be shown within graphs and tables. Conclusions: 1. Posturography using Neurocom Balance Master is a suitable method to assess balance and coordination features in elite basketball players. 2. Specific posturography tests allow detection of injury risk factors, such as balance impairments. In this trial, the results belong to data obtained along the development of the project: "ViiP: Intelligent System for Isokinetic and Posturographical Analysing, Integration and Assess of the Spine", financed by the Ministry of Science and Innovation. Research Head Office Science and Technology I + D.